Combined cellular and biochemical profiling of Bruton’s tyrosine kinase inhibitor nemtabrutinib reveals potential application in MAPK-driven cancers - Kluitmans, Daphne J. F.; Melis, Janneke J. T. M.; van den Bossche, Esmee; Ytsma, Jacob; de Roos, Jeroen A. D. M.; van Linden, Oscar P. J.; Grobben, Yvonne; Kooijman, Jeffrey J.; Zaman, Guido J. R. (Frontiers in Oncology, 2025)
BackgroundNemtabrutinib is a reversible inhibitor of both wild-type and acquired resistance-related mutant BTK. Since nemtabrutinib biochemically inhibits various kinases, new drug response biomarkers, cross-reactivities and differentiators may be identified.MethodsNemtabrutinib was profiled in a large panel of cancer cell line viability assays. The sensitivity profile of nemtabrutinib was compared with the profiles of 135 kinase inhibitors across the same cell lines. Additionally, cell line sensitivity was related to gene mutation status, gene and protein expression levels, and gene dependency scores. Potential targets were explored using biochemical assays.ResultsSensitivity to nemtabrutinib is on average three times higher in BRAF-mutant versus wild-type cell lines. Consistently, the sensitivity profile of nemtabrutinib is similar to that of MEK, ERK and pan-RAF inhibitors. Furthermore, sensitivity to nemtabrutinib is correlated with high FGFR3 gene expression levels, high levels of phosphorylated MEK1 and genetic dependency on several mitogen-activated protein kinases (MAPK). Biochemical profiling confirms that nemtabrutinib inhibits several growth factor receptor tyrosine kinases and downregulates MAPK signaling via MEK. Molecular docking studies suggest that nemtabrutinib preferentially binds in the ATP-binding pocket of MEK1.ConclusionCombined cancer cell panel and biochemical profiling reveals previously underappreciated cross-reactivities of nemtabrutinib indicating a potential application in MAPK-driven cancers.